Changes in expression of lysosomal membrane proteins in leucocytes of cancer patients treated with tyrosine kinase inhibitors - Pastvova, N; Havlasek, J; Dolezel, P; Kikalova, K; Studentova, H; Zemankova, A; Melichar, B; Mlejnek, P (Cancer chemotherapy and pharmacology, 2021)
Lysosomal sequestration of weak base drugs has been identified as one of the stress-related mechanisms that trigger in vitro lysosomal biogenesis controlled by transcription factor EB (TFEB). Whether such mechanism can induce lysosomal biogenesis in vivo is unknown. In this study, we addressed the question whether prolonged treatment with sunitinib (SUN) in patients with advanced renal cell carcinoma (n = 22) and with imatinib (IM) in those with gastrointestinal stromal tumor (n = 6) could induce lysosomal biogenesis in leukocytes. Lysosomal biogenesis was monitored using immunoblotting of three lysosomal membrane proteins: lysosome-associated membrane proteins 1 and 2 (LAMP1 and LAMP2) and vacuolar H+-ATPase, B2 subunit (ATP6V1B2). Present results indicate that prolonged treatment with SUN affects LAMP1 and LAMP2 expression only marginally in most patients. In contrast, changes in ATP6V1B2 expression were marked and resembled irregular oscillations. Very similar changes in the expression of lysosomal membrane proteins were also found in IM-treated patients. Conclusion: prolonged treatment of cancer patients with SUN and IM did not induce leucocyte lysosomal biogenesis but dramatically affected expression of ATP6V1B2.
Keywords: Carcinoma, Renal Cell; inhibitory proteinkinas; lidé; Imatinib; karcinom z renálních buněk; Female; Gastrointestinal Stromal Tumors; Lysosmal membrane proteins; gastrointestinální stromální tumory; transkripční faktory BHLH-Zip; Humans; Sunitinib; imatinib mesylát; sunitinib; LAMP2; B2 subunit; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; mužské pohlaví; membránové glykoproteiny asociované s lyzozomy; lyzozomy; Lysosomal Membrane Proteins; Vacuolar H+-ATPase; ženské pohlaví; Protein Kinase Inhibitors; Leukocytes; Lysosomes; Male; LAMP1; leukocyty; Imatinib Mesylate